ISLAMIC EDUCATION AND REINTEGRATION OF SCIENCES: Improving Islamic Higher Education - Azyumardi Azra (Media Syari'ah, 2017)
The Noble Prize Winner for Physics, Mohammed Abdus Salam, rightly maintains that there is almost no question that among all civilizations in the present time on this planet, science is weakest in the lands of Islam. In his opinion, the danger of this weakness cannot be underestimated since social development and even the survival of a society depends directly on its strength in science and technology in the condition of the present age. Therefore, Muslim societies have a little chance to survive in the very competitive age of globalization unless they seriously address this grave problem. The weaknesses of science in the Muslim world as whole can be seen in a number of rough indicators that are available since the 1980s when many Muslim countries began to modernize their economy. By and large, up until today, Muslim countries are classified as ‘third world countries’; only few of them can be included among developing countries, let alone ‘developed’ and ‘advanced’ countries. As a result, there is a lot of retardation of social development in the Muslim world.